Appendicitis in Pregnancy: An Updated Review for Healthcare Professionals and The Main Roles of Emergency Professionals - Alonizi , Hind Hussein; Alotaibi, Bader Ali; Alrashidi, Dheifallah Saud; Alfaqeeh , Ghadah Ahmad; Alasmari , Adel Sarhan Awadh; Alqahtani , Saeed Mohammed Muhy; Alghurab, Adel Mohammed; Al Onazi, Saleh Khalaf Jadhan; Amer M, Albariqi, Ahmed; Alanazi, Amjad Mohammed; Albalawi, Taghreed Saad Salim; Alatawi, Hanan Sameer; et al. (Journal of Ecohumanism, 2024)
Background: Acute appendicitis is the most common non-obstetric surgical condition during pregnancy, requiring prompt diagnosis and management to prevent complications such as perforation, peritonitis, and preterm labor. Diagnosing appendicitis in pregnancy is challenging due to physiological changes, including displacement of the appendix and overlapping symptoms with pregnancy-related conditions. Imaging techniques like ultrasound and MRI are preferred to minimize fetal radiation exposure, and surgical intervention, particularly laparoscopic appendectomy, is the primary treatment. Aim: This review aims to provide an updated overview of the diagnosis, management, and treatment of acute appendicitis in pregnant patients, emphasizing the roles of emergency professionals in ensuring timely and effective care. Methods: The review synthesizes current literature on the etiology, epidemiology, pathophysiology, and diagnostic challenges of acute appendicitis in pregnancy. It evaluates the roles of clinical assessment, laboratory testing, and imaging modalities, including ultrasound, CT, and MRI. The review also discusses surgical and nonsurgical management strategies, highlighting the importance of a multidisciplinary approach involving obstetricians, surgeons, and anesthesiologists. Results: Acute appendicitis in pregnancy presents atypically due to anatomical and physiological changes, complicating diagnosis. Ultrasound and MRI are safe and effective imaging tools, while laparoscopic appendectomy is the preferred surgical approach, though open surgery may be necessary in advanced pregnancy. Delayed diagnosis increases the risk of complications, including perforation and preterm labor. A multidisciplinary approach is essential for optimizing maternal and fetal outcomes. Conclusion: Timely diagnosis and treatment of acute appendicitis in pregnancy are critical to minimizing risks to both mother and fetus. Emergency professionals play a pivotal role in early recognition, diagnostic imaging, and coordination of care. A multidisciplinary approach, combined with appropriate imaging and surgical intervention, ensures optimal outcomes